2020
DOI: 10.5194/amt-13-2057-2020
|View full text |Cite
|
Sign up to set email alerts
|

Eddy covariance flux measurements of gaseous elemental mercury over a grassland

Abstract: Direct measurements of the net ecosystem exchange (NEE) of gaseous elemental mercury (Hg 0 ) are important to improve our understanding of global Hg cycling and, ultimately, human and wildlife Hg exposure. The lack of long-term, ecosystem-scale measurements causes large uncertainties in Hg 0 flux estimates. It currently remains unclear whether terrestrial ecosystems are net sinks or sources of atmospheric Hg 0 . Here, we show a detailed validation of direct Hg 0 flux measurements based on the eddy covariance t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 92 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…Reduced CO 2 uptake is evident by the slight dip in CO 2 diel flux compared to the stronger diel trends observed in other seasons. Osterwalder et al (2020), observed a similar phenomenon where drought conditions at a grassland site in Switzerland resulted in reduced CO 2 and Hg stomatal uptake. As intense drought conditions are a defining feature of Australia's environment it is plausible that during drought Australia's grasslands could become a greater source of atmospheric Hg.…”
Section: Mercury Flux Variation Across Seasonsmentioning
confidence: 65%
“…Reduced CO 2 uptake is evident by the slight dip in CO 2 diel flux compared to the stronger diel trends observed in other seasons. Osterwalder et al (2020), observed a similar phenomenon where drought conditions at a grassland site in Switzerland resulted in reduced CO 2 and Hg stomatal uptake. As intense drought conditions are a defining feature of Australia's environment it is plausible that during drought Australia's grasslands could become a greater source of atmospheric Hg.…”
Section: Mercury Flux Variation Across Seasonsmentioning
confidence: 65%
“…However, before we are able to discuss consequences of using a cubic wind speed parameterizations of k Hg in detail, we need more long‐term, direct Hg 0 flux measurements, across a greater range of wind speeds. The recent presentation of the first eddy covariance system with sufficient accuracy to measure Hg 0 land‐atmosphere exchange over natural surfaces (Osterwalder et al., 2020) might be more easily applied to measure air‐sea Hg 0 exchange than the more technically challenging REA method used in this study. Before applying this novel eddy covariance method for Hg over oceans, though, the accuracy will need to be improved compared to what was achieved in the premier application of this method, given the generally lower gradients over water than land.…”
Section: Discussionmentioning
confidence: 99%
“…We need multi‐seasonal Hg 0 flux time series to make statistically significant estimates of the dependence of fluxes on other environmental parameters, including complementary observations relevant to hypothesized explanations such as the role of sea spray aerosol emission, occurrence of biological surface films or bubble formation. This can be done with direct Hg 0 flux measurements on islands, floating instrument platforms or research vessels using the newly available eddy covariance technique (Osterwalder et al., 2020). If there is indeed a stronger cubic wind speed dependence for k Hg , similar to that of O 2 which also has low solubility, there will be a need to reevaluate the understanding and modeling of Hg 0 flux processes at local, regional and global scales.…”
Section: Discussionmentioning
confidence: 99%
“…Unique features of the monitor, which provided direct real-time measurement with frequency of 15 times per second readings, were used for the specific mercury surface to air mercury flux calculation (Osterwalder et al, 2020).The monitor can also be used in applications when the analysed ambient air has a reduced pressure, down to 40 kPa (at an altitude up to 5300 m or in the plane measurements (Weigelt et al, 2016)). Since the monitor does not require consumables, including gas cylinders, the use of RA-915AM monitors makes it possible to simplify maintenance at high-altitude and remote monitoring stations.…”
Section: Methodsmentioning
confidence: 99%